2009
DOI: 10.1002/j.2055-2335.2009.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel Exposure and its Effective Decontamination

Abstract: Background: Apart from generic guidelines for the safe handling of cytotoxic drugs in pharmacy departments, there is no specific published literature pertaining to cleaning procedures and inadvertent exposure to paclitaxel. Aim: To examine occupational exposure to paclitaxel; to identify an effective decontamination reagent; and to determine suitable glove type for skin protection. Method: 8 decontamination reagents were tested for paclitaxel degradation. Air sampling filters, Ghost Wipes and cotton wipes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…While sodium hypochlorite can cause discomfort to users in a room that is poorly ventilated, it should not be an issue in pharmacy cleanrooms where there are between 20 and 60 room air changes per hour. Numerous studies have been carried out with the aim of identifying an effective cleaning product able to decontaminate a surface contaminated with HDs [6][7][8][9][10][11][12][13]. Sodium hypochlorite alone or combined with sodium thiosulfate, hydrogen peroxide, potassium permanganate, isopropyl alcohol and Fenton reagent were among the most tested products.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While sodium hypochlorite can cause discomfort to users in a room that is poorly ventilated, it should not be an issue in pharmacy cleanrooms where there are between 20 and 60 room air changes per hour. Numerous studies have been carried out with the aim of identifying an effective cleaning product able to decontaminate a surface contaminated with HDs [6][7][8][9][10][11][12][13]. Sodium hypochlorite alone or combined with sodium thiosulfate, hydrogen peroxide, potassium permanganate, isopropyl alcohol and Fenton reagent were among the most tested products.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been demonstrated that it can eliminate up to 98 % of the contamination on surfaces exposed to methotrexate, cytarabine, gemcitabine, etoposide phosphate, irinotecan, CP, ifosfamide, doxorubicin, epirubicin, and vincristine [7]. However, sodium hypochlorite can damage surfaces, may irritate the respiratory tract of exposed staff and is also potentially genotoxic for humans [12]. Touzin et al showed that a combination of sodium hypochlorite and sodium thiosulfate reduced 99.8 % of a contaminated area exposed to CP and that itcould theoretically prevent damage to surfaces [8].…”
Section: Discussionmentioning
confidence: 99%
“…It is of utmost importance that an effective post drug-preparation cleaning procedure is carried out in these workstations in order to limit the accumulation of residual contamination, both chemical and microbiological. Several studies have been published on different cleaning procedures for surfaces contaminated by antineoplastic agents (Roberts et al, 2006;Lee et al, 2009;Queruau Lamerie et al, 2013;Le et al, 2013). Decontamination protocols involving sodium hypochlorite were considered effective for a variety of active ingredients, but they could damaged cleaned surfaces (need for rinsing after use) and were potentially genotoxic (Lee et al, 2009;Sharma et al, 2013).…”
mentioning
confidence: 99%
“…Several studies have been published on different cleaning procedures for surfaces contaminated by antineoplastic agents (Roberts et al, 2006;Lee et al, 2009;Queruau Lamerie et al, 2013;Le et al, 2013). Decontamination protocols involving sodium hypochlorite were considered effective for a variety of active ingredients, but they could damaged cleaned surfaces (need for rinsing after use) and were potentially genotoxic (Lee et al, 2009;Sharma et al, 2013). Hydrogen peroxide, whether liquid or vaporized (VHP®), showed good decontamination and degradation action on 5-Fluorouracil, doxorubicin (DOX), and cyclophosphamide (CP) (Roberts et al, 2006).…”
mentioning
confidence: 99%
“…Desorption strategies were studied on different antineoplastic drugs after intentional surface contamination. Some studies focused on 1 or 2 drugs [27][28][29][30][31][32], testing solutions of different natures (quaternary ammonium, biguanide, alcohol-based solutions). Others were performed on 10 drugs with a wider range of solutions (organic solvent; anionic, non-ionic or cationic surfactants; oxidant or water) [33].…”
Section: Introductionmentioning
confidence: 99%